2014
DOI: 10.1155/2014/252307
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Guidelines: A National Audit of the Management of Acute upper Gastrointestinal Bleeding. The REASON Registry

Abstract: There was variability between the process of care and 'best practice' in NVUGIB. Certain patient and situational characteristics may influence guideline adherence. Dissemination initiatives must identify and focus on such considerations to improve quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
0
22
0
3
Order By: Relevance
“…Similarly, other contemporary studies from Australia and Europe have also reported high rates of non‐ulcer‐related bleeding, exceeding peptic ulcer disease . Even in studies where ulcer‐related bleeding was the most common cause, more than a third of cases were still from non‐ulcer‐related aetiologies . As such, non‐ulcer‐related bleeding is important, and to our knowledge, this is the largest study to date reporting on outcomes after non‐ulcer‐related NVUGIB and their determinants.…”
Section: Discussionmentioning
confidence: 57%
“…Similarly, other contemporary studies from Australia and Europe have also reported high rates of non‐ulcer‐related bleeding, exceeding peptic ulcer disease . Even in studies where ulcer‐related bleeding was the most common cause, more than a third of cases were still from non‐ulcer‐related aetiologies . As such, non‐ulcer‐related bleeding is important, and to our knowledge, this is the largest study to date reporting on outcomes after non‐ulcer‐related NVUGIB and their determinants.…”
Section: Discussionmentioning
confidence: 57%
“…Geographic differences in Helicobacter pylori colonization and susceptibility have previously been described [26]. In addition, there is clearly a variation in the way in which endoscopists manage upper gastrointestinal bleeding [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Estos niveles de adherencia y su variabilidad no son diferentes de lo publicado internacionalmente respecto de la adherencia a recomendaciones en distintas áreas clínicas 19,20 . Esta similitud con otros estudios sumada a la concordancia satisfactoria en la auditoria "doble" realizada a una submuestra de los registros apoya la confiabilidad en las mediciones de adherencia realizadas en el estudio.…”
Section: Principales Hallazgosunclassified